A User‐Oriented Method for Preferential Color Scheme Generation. Issue 2 (4th December 2013) - Hu, Guosheng; Zhang, Mingmin; Pan, Zhigeng; Lin, Ling; Rhalibi, Abdennour E. L.; Song, Jianwen
Abstract Harmony and preference are two important factors in constructing color combination for the purpose of color design. We presented a method for generating harmonious color scheme in a previous project. As an extension to the project, we propose here a method for generating color schemes that are based on user's preference. We considered color combinations as a set of color relations rather than a summation of specific color components (color elements); and we derived a model of six‐variable color relations, representative value of hue, representative value of saturation, representative value of lightness, span of hue, span of saturation, and span of lightness. With this model, color combinations can be expressed as specific parameters of the six‐variable model. Individual preferences are represented as certain parameters, from which new color schemes can be reconstructed to meet individual requirements. An interactive system for generating preferential color schemes is built with all these principles integrated. As a color design toolkit for user study, the system accesses user's preference features for color combinations, and provides new color schemes that fit the user's need. User study shows that both professionals and novices can generally acquire preferential color schemes of their own. © 2013 Wiley Periodicals, Inc. Col Res Appl, 40, 147–156, 2015